Lung transplantation in Australia, 1986–2018: more than 30 years in the making. Issue 10 (4th June 2018) - Paraskeva, Miranda A; Levin, Kovi C; Westall, Glen P; Snell, Gregory I
Summary:   Lung transplantation in Australia is 32 years old in 2018. From its early infancy in 1986, it continues to evolve and is internationally recognised as demonstrating world's best practices in organ donation, utilisation and transplantation procedures. Over the past decade, transplant numbers have increased substantially due to innovations in donor procurement, such as donation after circulatory death, the use of ex vivo lung perfusion, extended criteria and organ utilisation, with more than 200 lung transplants undertaken in Australia annually. Parallel to this, lung transplant outcomes have continued to improve. While the management of lung transplant recipients is heavily dependent on a tertiary care paradigm, this model is well developed and has been extremely successful, with Australian outcomes exceeding those of the International Society for Heart and Lung Transplantation Registry at all time points.